THE ROLE OF MODERN SPORTS TRAINING IN DEVELOPING PHYSICAL ENDURANCE IN STUDENTS (World Bulletin of Physical Education and Sports Science, 2026)
This article examines the role of modern sports training in developing physical endurance in students within the context of pedagogical higher education. Physical endurance is regarded as one of the key components of students’ general fitness, health stability, and readiness for sustained academic and professional activity. In contemporary educational conditions, the improvement of endurance requires not only traditional exercise methods but also scientifically grounded training technologies based on gradual progression, individualization, functional monitoring, and motivational support. The study highlights that modern sports training contributes to the development of cardiovascular efficiency, respiratory capacity, muscular stamina, and adaptive reserves of the body. It also creates favorable conditions for strengthening self-discipline, stress resistance, and active participation in physical culture. Special attention is given to the pedagogical value of systematic training programs, interval exercises, circuit methods, mixed aerobic and anaerobic loads, and digital tools for tracking performance indicators. The article argues that the integration of modern training approaches into university sports practice increases the effectiveness of endurance development and supports the formation of healthy lifestyle habits among students. The findings may be used in improving the content of physical education classes, extracurricular sports activities, and methodological support for future specialists in sports pedagogy.
Keywords: Physical endurance, sports training, students, physical education, motor activity, training methods, functional readiness, health promotion, pedagogical effectiveness, fitness development.